Development and Application of a Sustainable Management System for Unpaved Rural Road Networks. Issue 12 (December 2019) - Chamorro, Alondra; Tighe, Susan
For the sustainable management of rural roads, social, institutional, technical, economic and environmental aspects should be considered under a long-term perspective. The current practice in developing countries is that only some of these key sustainable aspects are considered in the management process. In addition, rural roads maintenance management is commonly performed under a short-term basis, not considering the life-cycle costs and benefits in the economic analysis and project prioritization. This paper presents the development of a sustainable management system for rural road networks and its application in developing countries. The approach considers the development of a sustainable framework, application of a network-level condition evaluation methodology, condition performance models for gravel and earth roads, cost-effective maintenance standards, a long-term prioritization procedure that accounts for sustainable aspects, and a computer tool that integrates the system components. The management system has been applied and validated in two unpaved rural road networks in developing countries, located in Chile and Paraguay. Sensitivity analysis was carried out to assess the impacts of input parameters in the performance of developed system. As a result of the research an adaptable and adoptable sustainable management system for rural networks has been developed to assist local road agencies in developing countries.